(untitled) (Revista Iberoamericana de Bioética, 2022)
The continuous and accelerated ageing of the population in modern societies has become a growing concern, due to the economic and social difficulties to ensure that the elderly’s basic and care needs are met. Suggestions for successful, active and healthy ageing with intrinsic capacities are all elitist strategies only available to people who have led prosperous lives replete with well-being and are simply unattainable for the majority in a worldwide context of growing inequality. A different proposal is suggested here, based on the recognition that ageing leads to a deterioration of the transcendental anthropologic traits of all human beings: relationality, immanent transcendence, and transcendence of the self. These factors require personal recognition and care from social caregivers who diagnose the specific needs of each person, and provide institutional care that is adapted to each case, in order to provide tolerable ageing that all can attain, thus avoiding the inequalities of elitist ageing proposals unavailable to the vast majority.